Tax reform strategies to strengthen Indonesia’s digital economy contribution - Iman Supriadi; Mochamad Fatchurrohman; Etin Puspita Sari (Review of Management, Accounting, and Business Studies, 2025)
This research aims to deeply investigate tax strategies and policies to increase the tax ratio in Indonesia, especially in the face of increasingly complex dynamics of the digital economy and global fragmentation. Using a descriptive and qualitative analytical approach, through literature studies, secondary data analysis, and case studies, this research aims to identify crucial obstacles in the taxation domain, formulate effective strategies to increase the tax ratio, and scientifically evaluate their impact. The results of the research highlight the state of Indonesian taxation, the strategies that can be applied to increase the tax ratio, as well as scientific contributions through the development of new concepts and the application of sustainable taxation strategies. The contribution of this paper lies in the formulation of policy recommendations that are not only theory-based but also supported by empirical evidence, in order to strengthen the foundation of Indonesia's tax system. In addition, this study provides direction for further research in the field of taxation and economics, directing future research agendas to deepen understanding and develop more effective policies in the face of changing global taxation dynamics.